Metode Pembelajaran Tutor Teman Sebaya Meningkatkan Hasil Belajar Berdasar Regulasi-Diri - Arjanggi, Ruseno; Suprihatin, Titin (UI Scholars Hub, 2010)
The purpose of this study is to empirically examine the effectiveness of peer tutoring method on self-regulated learning. In self-regulated processes such as planning, self monitoring, and control of disturbances, the model of interaction between personal environment and behavior is a reciprocal interaction. Peer tutoring is expected to raise the potential behavior through an independent learning materials organization. Those behaviours include assistance-seeking behavior and assistance-giving during a more intensive learning process resulted from nearer psychological distance between the tutor and tutee. The subject of this research was 63 students of the Faculty of Psychology Unissula Semarang, which was divided into two groups: 31 students in the control group and 32 students in the treatment group. The treatment group consisted of nine tutorial groups in which each group consisted of 3-4 students. This research used a motivated strategy for learning questionnaire. Analysis of variance is used to test the hypothesis. The result indicates that there is a positive effect of peer tutoring learning methods on self-regulated learning. Peer tutoring learning method has accounted for 17.4 per cent improvement learning based on student self regulation. This research proved that active learning can be done without involving a lot of teachers. Besides, the learning process can be maximized with the existing potentials by, among others, through peer tutoring